Place attachment, wellbeing, and conservation in surf destination communities - Mach, Leon; Rothrock, Elizabeth; Stark, Sydney; Nahmias, Jacob (Frontiers in Sustainable Tourism, 2024)
Frequently visited surf breaks are nested within unique ecosystems that face many underappreciated threats. This manuscript first explores the contribution of surfing to local wellbeing and analyses how wellbeing is impacted by different threats to surf ecosystems. The second aim is to gather local knowledge of, and desires for surf break protection in Bocas del Toro, Panama. Through qualitative interviews (N = 17) and surveys (N = 46), findings suggest that place attachment is tied to frequently visited surf breaks and is strongly correlated to the wellbeing derived from surfing. Surfing was also found to be the main reason 68% of the respondents moved to the archipelago. Length of time residing in Bocas, however, was not a predictor of place attachment. This might suggest that people migrate for certain aspects of surf ecosystems and that place attachment can perhaps be selected for and grow through experiences. Positive surfing experiences were also found to be under threat from several converging challenges related to sea level rise, coastal development, declining reef health, and overcrowding. Local surfers recognize that these threats are tied to global forces but seem more reactive in their fight to alleviate imminent visible threats. This research emphasizes the urgent need for dedicated institutions to effectively preserve frequently visited surf ecosystems in areas that are neither covered by global non-governmental surf protection organization campaigns nor dedicated legal protection frameworks. We also call for more attention dedicated to understanding how the benefits of surfing are nuanced, context based and tied to vulnerable places.